2018
DOI: 10.1177/1076029618808922
|View full text |Cite
|
Sign up to set email alerts
|

A New Model for Risk Stratification of Patients With Acute Pulmonary Embolism

Abstract: Pulmonary embolism (PE) is associated with mortality. There are many clinical prediction tools to predict early mortality in acute PE but little consensus on which is best. Our study aims to validate existing prediction tools and derive a predictive model that can be applied to all patients with acute PE in both inpatient and outpatient settings. This is a retrospective cohort study of patients with acute PE. For each patient, the Pulmonary Embolism Severity Index (PESI), simplified PESI (sPESI), European Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Other authors also reported lower APE patient mortality than we found in our study. For example a 1.2% mortality rate among low-risk APE patients classified using PESI and sPESI score [10], a 6.4% 30-day adverse outcome rate among normotensive (non-high-risk) patients [16], a 7.7-10% 30-day mortality rate in the overall group [17,18], and a 2.1% and 23.0% mortality rate for low-and high-risk APE patients [7]. Ebner et al [19] and Soriano et al [20] showed similar rates to those observed by us for in-hospital all-cause mortality, which in their studies amounted to 12.2% for the overall patient cohort [19], 3.25% for an sPESI score of 0 and 19.51% for an sPESI score ≥ 1, and 20% among those with a high-risk PESI score (classes III-V) [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors also reported lower APE patient mortality than we found in our study. For example a 1.2% mortality rate among low-risk APE patients classified using PESI and sPESI score [10], a 6.4% 30-day adverse outcome rate among normotensive (non-high-risk) patients [16], a 7.7-10% 30-day mortality rate in the overall group [17,18], and a 2.1% and 23.0% mortality rate for low-and high-risk APE patients [7]. Ebner et al [19] and Soriano et al [20] showed similar rates to those observed by us for in-hospital all-cause mortality, which in their studies amounted to 12.2% for the overall patient cohort [19], 3.25% for an sPESI score of 0 and 19.51% for an sPESI score ≥ 1, and 20% among those with a high-risk PESI score (classes III-V) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Such tools include: (a) calculation of Pulmonary Embolism Severity Index (PESI) or simplified PESI (sPESI) scores and the patient's qualification to one of five PESI risk classes or to one of two sPESI classes; (b) ESC classification of pulmonary embolism severity and the risk of early death (low/intermediate-low/intermediate-high/high); (c) determination of blood high-sensitivity troponin I (hs-TNI) or high-sensitivity troponin T (hs-TNT) concentration cut-offs (standard and age-adjusted); (d) assessment for signs of right ventricular (RV) pressure overload in transthoracic echocardiography (TTE) or RV enlargement in CTPA; and, in some cases, (e) determination of blood N-terminal proBtype natriuretic peptide (NT-proBNP) concentration cut-off (mostly ≥ 600 pg/ml) [2,3]. Researchers have also suggested using the following stratifying tools: the presence of coexisting DVT in patients at intermediate-low risk of short-term complications [5]; (b) selected parameters of CTPA imaging [6][7][8], as well as various combinations of the parameters, some of which are mentioned above, such as (i) D-dimer cut-off with sPESI [9], (ii) PESI with NT-proBNP, hs-TNT, and high-sensitivity C-reactive protein cut-offs [10] and (iii) PESI, sPESI and Bova scores with additional patient stratification on the basis of systolic blood pressure [11]; and (c) a combination of a quick Sequential Organ Failure Assessment (qSOFA) score with particular ECG signs [12].…”
Section: Introductionmentioning
confidence: 99%
“…В настоящем исследовании установлено, что на годовом этапе наблюдения у пациентов, перенесших ТЭЛА, летальность составляет 11,8%. Самой распространенной причиной смерти являлось повторное развитие ТЭЛА (в 36,4% случаев), что согласуется с результатами исследования, опубликованными в 2018 году, в котором рецидив ТЭЛА являлся причиной 27,3% смертей, на втором месте причиной летальных исходов являлось наличие онкопатологии (21,2%), равно как и в представленном нами исследовании [11]. Однако в отличие от нашего исследования авторами было отмечено три случая фатальных кровотечений.…”
Section: Discussionunclassified
“…These findings were confirmed in a subsequent analysis in a prospective cohort of hemodynamically stable patients with acute PE, showing that PE-related mortality was as high as 0.8% in low-risk patients, while it was virtually identical in intermediate-low and intermediatehigh-risk patients (i.e., 7.1 and 7.7%, respectively). 23 Other studies have demonstrated that the efficiency of the 2014 ESC model for predicting death and other unfavorable outcomes might be relatively unsatisfactory (i.e., < 80%), 24 since sPESI may misclassify a significant percentage of low-risk patients as higher risk, 25 recurrence can be as high as 4% in low-risk patients, 26 and out of hospital management of all hemodynamically stable PE patients is associated with a decreased risk of adverse events compared with hospitalization irrespective of the baseline clinical risk. 27 These recent data, along with the recent meta-analysis concluding that relying only on sPESI to classify patients in the low-risk category would be associated with an unacceptable mortality rate (i.e., between 0.9 and 2.5%), 28 raise renewed interest on the utility of hs-cTn testing being systematically performed in all patients with PE, regardless of their baseline clinical risk.…”
Section: Pulmonary Embolismmentioning
confidence: 99%